A Review on Cloud-based Privacy Preserving Schemes for Smart Meters - Alam, Muhammad Tanvir (INFOCOMP Journal of Computer Science, 2016)
Smart meters are used to have efficient energy management by the utilities using information driven approach. The requirements of scalable, elastic, reliable and shareable resources for deploying and running a Smart Grid utility’s software architecture strongly fits within the capabilities provided by Cloud platforms. Indeed, some data warehouse vendors are already considering Cloud deployments for Smart utilities. However, a growing concern is ensuring privacy of personally identifiable data within the information integration platform of the utility provider in an area. In this survey, we present a synthesized overview of existing works integrating cloud computing in the existing smart grid architecture, in order to have client privacy preserved for energy supply. Also, we compare and evaluate these privacy preserving solutions against feasibility and practicality.